A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae) - Yan, Chuncai; Zhao, Guangjun; Liu, Ting; Guo, Qin; Hou, Ziyuan; Wang, Xinhua; Pan, Baoping (Zootaxa, 2016)
Two new species of the genus Cryptochironomus Kieffer, C. maculus Yan & Wang sp. n. and C. protuberans Yan & Wang sp. n. are described and illustrated as adult males. C. albofasciatus (Staeger) is recorded from China for the first time. A key to the males of Cryptochironomus in China is presented and generic diagnosis is emended.